2015
DOI: 10.1007/s40618-015-0251-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to polychlorinated biphenyls and hexachlorobenzene, semen quality and testicular cancer risk

Abstract: The International Agency for Research on Cancer recently included dioxin-like polychlorinated biphenyls (PCBs) in Group 1 of known human carcinogens. Our study confirmed and identified various risk factors for testicular cancer: cryptorchidism, consumption of milk and dairy products, parents' occupation and serum concentration of hexachlorobenzene and PCBs and, for the first time, we showed the correlation between semen quality and the serum concentration of these pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 34 publications
1
44
0
2
Order By: Relevance
“…Decrease in epididymal sperm count was demonstrated in many other experimental studies [4549]. Recent longitudinal epidemiological studies also have shown associations between serum concentrations of DLCs and decreased semen parameters [13,5053] (Table 1). The Mocarelli group investigated acutely exposed men to high level of TCDD in Seveso, Italy, during different periods of onto-genies: perinatal, infancy/prepuberty (1–9 years), puberty (10–17 years), and adulthood (18–26 years).…”
Section: Dioxins and Male Reproductive Healthmentioning
confidence: 64%
“…Decrease in epididymal sperm count was demonstrated in many other experimental studies [4549]. Recent longitudinal epidemiological studies also have shown associations between serum concentrations of DLCs and decreased semen parameters [13,5053] (Table 1). The Mocarelli group investigated acutely exposed men to high level of TCDD in Seveso, Italy, during different periods of onto-genies: perinatal, infancy/prepuberty (1–9 years), puberty (10–17 years), and adulthood (18–26 years).…”
Section: Dioxins and Male Reproductive Healthmentioning
confidence: 64%
“…Environmental exposure to endocrine disrupting chemicals, including HCB, have been suggested as a risk factor for male genital abnormalities such as hypospadias (Rignell-Hydbom et al, 2012;Krysiak-Baltyn et al, 2012). A recent study showed for the first time a correlation between serum concentration of HCB and semen quality (Paoli et al, 2015). Regarding its potential links to cancer, these results are supported by the International Agency for Research on Cancer and the U.S. EPA that classify HCB as a probable human carcinogen (U.S. EPA, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…negli animali, essi possono agire sul sistema ormonale e compromettere la riproduzione ma i dati sulla fauna selvatica non sono conclusivi; 2. la presenza di EDC è stata associata ad aumento di disturbi riproduttivi, di alcuni tipi di cancro, malattie metaboliche come obesità e diabete, e malattie cardiovascolari [1][2][3][4][5]. Benché i risultati dei diversi studi siano coerenti con la tesi che accusa gli EDC, in pratica non è possibile documentare una relazione causale tra esposizione a un EDC ed effetto sull'organismo umano [6]; 3. le ricerche sono necessarie per valutare in modo completo i rischi, in particolare gli effetti tossici a bassa concentrazione e il cosiddetto "effetto cocktail" della esposizione a gruppi di sostanze; 4. alcuni EDC noti sono già disciplinati dalla legislazione per motivi che esulano dalla loro attività ormonale (tossicità generale, cancerogenicità, tossicità riproduttiva) [7].…”
Section: Stato Dell'arteunclassified